Principals' managerial skills in creating effective schools : perception of teachers at selected high schools in Padangsidempuan Town, North Sumatra Province, Indonesia - Zubaidah
This study investigates teachers' perception toward principals' managerial skills in creating effective schools at selected high schools in Padangsidempuan Town, North Sumatra Province, Indonesia. This study also investigates whether teachers' demographic characteristics (i.e. age, gender and years of teaching experience) affect their perceptions toward principals' managerial skills. This study considers three managerial skills, which include the conceptual, human relation and technical skills. The study is quantitative-descriptive in nature, employing the survey method in which questionnaireswere distributed to teachers in eight selected high schools in Padangsidempuan. The total population in this study was 489 teachers, while the total sample was 220 teachers. The study used simple random sampling technique whereby 25-30 teachers per school were selected. For data collection, a scale measuring the principals' managerial skills developed by Daniel Katz (2002) was used. This scale has two parts; the first part is allocated for the respondents' demographic information; and second part consists of 62 items with a 5-point Likert scale, (1 = strongly disagree and 5= strongly agree). The descriptive statistics )means, standard deviations and frequencies), independent samples t-test, one-way ANOVA test were performed to analyse the data. The study results have revealed that the overall mean score for principals' managerial skills was 4.18, meaning that the respondents generally agreed on all items, and the school principals applied the three components of managerial skills in their respective schools. More specifically, (1) the conceptual skills scored the highest mean score, (M= 4.36), followed by (2) the technical skills (M= 4.10) and (3) the human relation skills (M= 4.08). The study also revealed that there was no significant difference in the teachers' perception toward principals' managerial skills due to the respondents' gender and teaching experience. This study serves as an important tool to examine and measure the impact of principals' managerial skills in creating effective schools on school achievement as perceived by teachers. Eventually, this study provides valuable insights into the strategic development processes and approaches utilised by effective educational leaders towards the betterment of the nation.